Influence of Surface Modification of BaTiO3 Nanoparticles by Sodium Oleate and Chitosan on their Optical Properties and Agglomeration in Aqueous Solutions - Roldan López, Jose Luis (2021)
Spherical titanium barium nanoparticles with an average size about 100 nm in the tetragonal crystal phase were obtained by peroxide synthesis. To prevent their agglomeration and reduce the toxic effect, the surface of nanoparticles was chemically modified with sodium oleate and chitosan. Influence of surface modification by these compounds on agglomeration of nanoparticles in aqueous solutions, their spectral features, as well as generation of the second optical harmonic were investigated.